Understanding patient and physician perceptions of male androgenetic alopecia treatments in Asia–Pacific and Latin America. Issue 8 (31st March 2017) - Lulic, Zrinka; Inui, Shigeki; Sim, Woo‐Young; Kang, Hoon; Choi, Gwang Seong; Hong, Woosung; Hatanaka, Toshiki; Wilson, Timothy; Manyak, Michael
Abstract: This survey aimed to explore patient and physician attitudes towards male androgenetic alopecia (AGA), satisfaction with currently available male AGA treatments and investigate the factors affecting treatment choice. The survey was carried out in five countries (Japan, South Korea, Taiwan, Mexico and Brazil) between November and December 2015 using a standard market research methodology. Questionnaires were completed by patients with male AGA or hair loss/thinning and practicing physicians who were responsible for prescribing AGA treatment. In total, 835 patients and 338 physicians completed the questionnaire. Overall, 37.6% of patients reported satisfaction with the treatments they had used. The highest patient satisfaction was reported for 5‐alpha‐reductase inhibitors (53.9% of patients satisfied). In all countries, physicians were more likely than patients to think that male AGA has a major impact on patient confidence (89.3% vs 70.4%, respectively). There was agreement by physicians and patients that male AGA patients who are involved in their treatment decisions have better outcomes. Patients who were satisfied with AGA treatments were more likely to have the level of involvement they desired in treatment decisions (69.1% of satisfied patients) than dissatisfied patients (56.4% of dissatisfied patients). This survey provides valuable insights into the attitudes of patients and physicians in Asia and Latin America about male AGA and its treatments. The survey identified areas of disconnect between physicians and patients regarding the impact of male AGA, treatment consultations and the importance of treatment attributes. It also highlights the need for physicians to spend sufficient time with patients discussing AGA treatment approaches.